Self-Esteem and Family Communication as Predictors of Satisfaction with Studies in University Students from the Southern Region of Peru - Victor Canqui; Josue Edison Turpo-Chaparro; Oscar Mamani-Benito; Ronald Castillo-Blanco; Nancy Casildo-Bedón; Renzo Carranza-Esteban (International Journal of Educational Psychology)
Family and personal factors play an essential role in the satisfaction with the studies of university students. In this sense, the objective of this research was to determine if self-esteem and family communication predict satisfaction with studies in university students from the Puno Region, Peru.  The methodology consisted of a cross-sectional and predictive design; 538 Peruvian university students of both sexes participated (69.1% men and 30.09% women) in 2022, whose ages ranged between 17 and 37 years (M = 20.43 and SD = 3.22). The instruments used were the Rosenberg self-esteem scale, the Olson Family Communication Scale (FCS), and the Merino Satisfaction Scale with the study. The results show that the proposed model had a good fit (X2 = 582.26, df = 224, p < .001, TLI = 941, CFI = .948, RMSEA = .055, RMR = .041), evidencing that self-esteem and family communication significantly predict (p < .001) satisfaction with the studies. In the discussion it is observed that self-esteem and family communication are significant predictors of satisfaction with studies in university students. Therefore, strategies to improve satisfaction with studies should be aimed at improving the self-esteem and communication of university students.